Peculiarities of Recovery of Peripheric Blood Indices in Recipients of Transfusion Medium of Umbilical Blood Cryopreserved Cells at Hemopoiesis Hypoplastic State in Haematological Clinic - Gaschuk, A. P.; Kalinichenko, T. A.; Glukhenka, G. T. (Problems of Cryobiology and Cryomedicine, 2005)
Peculiarities of recovery in peripheric blood indices when using trasfusion medium with cryopreserved nucleated cells of umbilical blood in patients with hemodepressive states in hematological clinic have been demonstrated.